Impact of military actions on the epizootic situation with the spread of rabies in animals in Kherson Oblast - Melnychuk, V.; Мельничук, В.; Yevstafieva, V.; Євстаф'єва, В.; Bilan, Maryna; Bilan, M. V.; Bilan, M.; Білан, Марина Володимирівна; Zazharskiy, Vladymyr; Zazharskiy, Volodymyr; Zazharskyi, Vladymyr; Zazharskyi, Volodymyr; et al. (Oles Honchar Dnipropetrovsk National University, 2024)
Rabies is a zoonotic disease caused by a neurotropic RNA virus of the Lyssavirus genus, recorded in various species of wild and domestic animals in many countries of the world, including Ukraine, where this disease has been continuosly diagnosed in animals and sporadically in people. Therefore, there is a need to study the epizootic specifics of rabies in different species of animals as potential sources of threat to people in individual administrative-territorial units of Ukraine. This becomes especially relevant against the background of martial law and the catastrophic flooding which took place in Kherson Oblast. Determining the peculiarities and manifestations of epizootic process of rabies in animals was conducted in the conditions of de-occupied territories of Kherson Oblast in 2023. During that year, 27 studies of samples of pathological/biological materials from animals suspected of rabies were conducted. Those included 24 samples from domestic animals – cattle (Bos taurus), dogs (Canis lupus familiaris), cats (Felis silvestris catus), and 3 from wild animals – fox (Vulpes vulpes) and jackals (Canis aureus). According to the results, rabies was confirmed in 88.9% of the total number of analyzed samples. Most often, rabies was diagnosed in domestic animals, particularly, dogs and cats – 45.8% and 29.2%, respectively. In the representatives of wild fauna, rabies was detected in 12.5% of the cases, in particular, 8.3% in foxes and 4.2% in jackals. The analysis of the seasonality of rabies morbidity in animals found no pattern in the dynamics. However, according to species, the peak of rabies in foxes took place in autumn, particularly, September and October. An important fact is that the bulk of rabies cases, acccounting for 91.7%, occurred in the period after the Kahovka Dam had been blown up by the Russian Federation. Territorially, during the surveillance period, rabies in animals was confirmed in 23 settlements of Kherson Oblast: 22 cases within the Oblast’s districts and one case in the city of Kherson proper. Сказ – це зоонозне захворювання, спричинене нейротропним РНК-вірусом роду Lyssavirus, зареєстрованим у різних видів диких та свійських тварин у багатьох країнах світу, зокрема в Україні, де це захворювання постійно діагностується у тварин та спорадично у людей. Тому існує потреба у вивченні епізоотичної специфіки сказу у різних видів тварин як потенційних джерел загрози для людей в окремих адміністративно-територіальних одиницях України. Це стає особливо актуальним на тлі воєнного стану та катастрофічної повені, що сталася в Херсонській області. Визначення особливостей та проявів епізоотичного процесу сказу у тварин проводилося в умовах деокупованих територій Херсонської області у 2023 році. Протягом цього року було проведено 27 досліджень зразків патологічних/біологічних матеріалів від тварин, підозрюваних у сказі. Серед них було 24 зразки від свійських тварин – великої рогатої худоби (Bos taurus), собак (Canis lupus familiaris), котів (Felis silvestris catus) та 3 від диких тварин – лисиць (Vulpes vulpes) та шакалів (Canis aureus). Згідно з результатами, сказ було підтверджено у 88,9% від загальної кількості проаналізованих зразків. Найчастіше сказ діагностували у свійських тварин, зокрема, собак та котів – 45,8% та 29,2% відповідно. У представників дикої фауни сказ виявляли у 12,5% випадків, зокрема, у 8,3% у лисиць та 4,2% у шакалів. Аналіз сезонності захворюваності на сказ у тварин не виявив закономірності в динаміці. Однак, за видами, пік сказу у лисиць припадав на осінь, зокрема, на вересень та жовтень. Важливим фактом є те, що основна кількість випадків сказу, що становило 91,7%, сталася в період після підриву Каховської греблі Російською Федерацією. Територіально, протягом періоду спостереження, сказ у тварин було підтверджено у 23 населених пунктах Херсонської області: 22 випадки в межах районів області та один випадок у власне місті Херсон.
Вплив військових дій на епізоотичну ситуацію з поширенням сказу серед тварин у Херсонській області
Білан Марина Володимирівна https://orcid.org/0000-0003-3178-201X Зажарський Володимир Володимирович https://orcid.org/0000-0003-2674-2494 Зажарська Надія Миколаївна https://orcid.org/0000-0002-8328-6440 Давиденко Павло Олександрович https://orcid.org/0000-0002-8425-3835
Keywords: seasonal dynamics of rabies; сезонна динаміка сказу; epidemiology of rabies; епідеміологія сказу; rabid animals; скажені тварини; domestic animals; свійські тварини; wild animals; дикі тварини